Optimal search strategies for retrieving systematic reviews from Medline: analytical survey - Montori, Victor M; Wilczynski, Nancy L; Morgan, Douglas; Haynes, R Brian (BMJ, 2005)
Abstract Objective: To develop optimal search strategies in Medline for retrieving systematic reviews. Design: Analytical survey. Data sources: 161 journals published in 2000 indexed in Medline. Main outcome measures: The sensitivity, specificity, and precision of retrieval of systematic reviews of 4862 unique terms in 782 485 combinations of one to five terms were determined by comparison with a hand search of all articles (the criterion standard) in 161 journals published during 2000 (49 028 articles). Results: Only 753 (1.5%) of the 49 028 articles were systematic reviews. The most sensitive strategy included five terms and had a sensitivity of 99.9% (95% confidence interval 99.6% to 100%) and a specificity of 52% (51.6% to 52.5%). The strategy that best minimised the difference between sensitivity and specificity had a sensitivity of 98% (97% to 99%) and specificity of 90.8% (90.5% to 91.1%). Highest precision for multiterm strategies, 57% (54% to 60%), was achieved at a sensitivity of 71% (68% to 74%). The term “cochrane database of systematic reviews.jn.” was the most precise single term search strategy (sensitivity of 56% (52% to 60%) and precision of 96% (94% to 98%)). These strategies are available through the “limit” screen of Ovid's search interface for Medline. Conclusions: Systematic reviews can be retrieved from Medline with close to perfect sensitivity or specificity, or with high precision, by using empirical search strategies.